2021
DOI: 10.1016/j.ensci.2021.100371
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating pain in Parkinson's disease: Its prevalence and impact on quality of life

Abstract: Pain is a common non-motor symptom in Parkinson's disease (PD) patients, and the incidence of fluctuating pain may be improved by taking levodopa. There are only a few detailed reports regarding fluctuating pain. In this study, 331 PD patients were classified into three groups: no-pain group (67.4%), non-fluctuating pain group (22.1%), and fluctuating pain group (10.6%). We evaluated patients' background and its impact on the quality of life (QOL) of each group. The pain group exhibited higher levels of depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…They found that patients with H&Y stage more than 2.5 had a higher percentage of fluctuation-related pain. [30] Another study demonstrated a lower frequency of fluctuation related pain with higher age of onset. [23] This could partially explain the high prevalence of fluctuation-related pain in our study since 50.5% of the patients had H&Y scores of more than 2.5 and 34.4 % had an early-onset PD.…”
Section: Discussionmentioning
confidence: 97%
“…They found that patients with H&Y stage more than 2.5 had a higher percentage of fluctuation-related pain. [30] Another study demonstrated a lower frequency of fluctuation related pain with higher age of onset. [23] This could partially explain the high prevalence of fluctuation-related pain in our study since 50.5% of the patients had H&Y scores of more than 2.5 and 34.4 % had an early-onset PD.…”
Section: Discussionmentioning
confidence: 97%